Secondary metabolites from the endophytic fungus Talaromyces pinophilus. Issue 15 (3rd August 2017) - Vinale, F.; Nicoletti, R.; Lacatena, F.; Marra, R.; Sacco, A.; Lombardi, N.; d'Errico, G.; Digilio, M. C.; Lorito, M.; Woo, S. L.
Abstract: Endophytic fungi have a great influence on plant health and growth, and are an important source of bioactive natural compounds. Organic extracts obtained from the culture filtrate of an endophytic strain of Talaromyces pinophilus isolated from strawberry tree ( Arbutus unedo ) were studied. Metabolomic analysis revealed the presence of three bioactive metabolites, the siderophore ferrirubin, the platelet-aggregation inhibitor herquline B and the antibiotic 3-O-methylfunicone. The latter was the major metabolite produced by this strain and displayed toxic effects against the pea aphid Acyrthosiphon pisum (Homoptera Aphidiidae). This toxicity represents an additional indication that the widespread endophytic occurrence of T. pinophilus may be related to a possible role in defensive mutualism. Moreover, the toxic activity on aphids could promote further study on 3-O-methylfunicone, or its derivatives, as an alternative to synthetic chemicals in agriculture. Abstract :